Web-Based Library Information System Using Rapid Application Development (RAD) Method at Qamarul Huda University - Valian Yoga Pudya Ardhana; Muhammad Sapi’i; Hasbullah Hasbullah; Eliyah A M Sampetoding (STMIK Budi Darma, 2022)
The library is an important part of higher education, where the teaching and learning process does not escape from teaching materials and reference materials. Qamarul Huda Badaruddin University is one of the universities in NTB which has a library with a desktop-based library system. This has an impact on the management of libraries and users which in this case students become ineffective and inefficient. With a high need for libraries, library managers, namely librarians and students as users, need a web-based information system so that they can be used from anywhere and anytime, simply using a smartphone or computer. To answer the above problems, the authors design and build a web-based library information system at Qamarul Huda Badaruddin University using the Rapid Application Development (RAD) method. The framework uses CodeIgniter which allows developers to create web applications with Rapid Application Development (RAD) development characteristics. The Qamarul Huda Badaruddin University Library Information System consists of 12 functional requirements, which cover all the requirements for the Qamarul Huda Badaruddin University library. Completion of each module also refers to all stages of the Rapid Application Development (RAD) method and all of them can run well